The Relationship Between Islamic Work Ethics And Employee Performance Among Medical Staff In The Public Health Sector In Bahrain: Employee Commitment As Mediating Variable - Ali Ahmed Ateeq Ali (Universiti Sains Islam Malaysia, 2024)
Matric: 4160151(FKP)